Determinants of commercial bank's non-performing loans in Bangladesh: An empirical evidence - Nazmoon Akhter (Cogent Economics & Finance, 2023)
Non-performing loan (NPL) is a red flag, providing signal of jeopardize for a country's economy. With respect to increase in NPLs, banking sector of Bangladesh has trapped in gridlock. This problem has become an alarming issue for bank's sustainability. The present study investigates the determinants of commercial bank's NPLs in Bangladesh. Due to data deficiency, the study collects data from 30 sampled commercial banks in Bangladesh over the period from 2011 to 2020, as during 2011, the total scheduled commercial banks in Bangladesh were 34. The study performs Random Effect Regression Model, Fixed Effect Regression Model, and one step GMM system to get the robust and significant result. The study reports that firm-specific factors like lag of NPLs, loan loss provision to total equity ratio, equity-to-total asset ratio, capital adequacy ratio, net loan to total deposit and borrowing ratio, return on equity, and macroeconomic factors such as inflation, and GDP ratio are the crucial determinants of NPLs in Bangladesh. The study concludes that commercial banks should operate its activities more efficiently and avoid reckless lending along with mandatory capital requirement in order to reduce NPLs and to ensure profit for their shareholders. The analysis of the study would provide insight guidelines regarding bank's credit risk management procedures and systems to country's regulatory body in order to design and adopt required prudential regulations in credit policy.
Keywords: 330; firm-specific and Macroeconomic factors; NPLs